The Changing Wage Return to an Undergraduate Education - Nigel C. O'Leary; Peter J. Sloane (Institute for the Study of Labor (IZA), 2005)
Between 1990/91 and 2000/01 the number of male undergraduates in Britain increased by over one-third while the number of female undergraduates has increased nearly twofold. Given this substantial increase in supply we would expect some impact on the wage premium for recent graduates unless demand has shifted in parallel. Following Katz and Murphy (1992), we adopt a simple supply and demand framework to analyse changes in earnings mark-ups across degree disciplines over time. Using a propensity score approach to match those graduates entering the labor market with an age balanced sample of individuals with two or more A-Levels from the Labour Force Survey, we find a significant decline in the markup for females, whilst no such change is apparent for males. These aggregate figures, however, mask a great deal of variation across degree subjects, with declines in those subjects in which women predominate and in the lowest quartile of the earnings distribution being identified. The results point to both supply and demand factors impacting on the graduate mark-up as theory would suggest.
Keywords: J0; I2; J3; 330; education; wages